Entrapment of the Brachial Artery Following Supracondylar Fracture Reduction: A Case Report - Seiied Mohammad Hashemie Amir; Ali Mohammadi Kali; Javad Boskabadi; Saeed Kargar Soleiman Abad; Mehdi Davoodi; Hossein Farsavian (Mazandaran University of Medical Sciences, 2021)
Background: Supracondylar fractures of the humerus are common elbow fractures in children. Supracondylar fractures have two subtypes: flexion, which makes up less than 2% of all such fractures, and extension, which makes up more than 98% of supracondylar fracture of the humerus. Supracondylar fractures of the humerus can develop vascular and neurological complications, either following the fracture itself due to the detached pieces of bone or after reduction or K-wire fixation therapy. The most common complication is damage to the brachial artery. Case Presentation: Our patient is a healthy 7-year-old right dominant boy who sustained a Gartland type III fracture following a fall and was admitted to the Emergency Ward. At first, a weak pulse was detected in the distal part of the right upper extremity. After the reduction using 2 K-wires, the distal pulse of the limb became undetectable. Vascular examination revealed that the adventitia of the brachial artery was trapped between the condyle parts. The artery was then released, and the distal pulse returned. Conclusions: This case shows that although entrapment and pulling of the adventitia of the brachial artery between the condyles of the humerus following a supracondylar fracture is a rare occurrence, it can happen in this type of fracture. After reduction using K-wires percutaneously, a neurovascular examination in all cases of supracondylar fractures is necessary. In supracondylar fractures with pink pulseless limbs, immediate arterial exploration can achieve a markedly better outcome than simply monitoring.